Evaluation of pre-exposure vaccine effectiveness against mpox during the 2022-2023 mpox outbreak in the Madrid region (Spain): a test-negative design - José Francisco Barbas del Buey; Jesús Íñigo Martínez; Marcos Alonso García; Andrés Aragón Peña; Laura Montero Morales; Araceli Arce Arnáez (BMJ Publishing Group, 2024)
Introduction An appropriate vaccination approach is critical to control the current outbreak of mpox but there is little research providing information on its effectiveness, particularly under circumstances of limited vaccine availability.Methods Pre-exposure vaccination campaign in the Madrid region, with the modified vaccinia Ankara-Bavarian Nordic was indicated in the risk groups from 18 July 2022.To evaluate the vaccine effectiveness (VE) of a dose of third-generation smallpox vaccine against mpox in the context of pre-exposure prophylaxis, a population-based indirect cohort study (Broome method) also known as test-negative design (TND) was conducted in the Madrid region (6 751 251 inhabitants). Logistic regression was used to obtain the adjusted VE in the TND with its time-response relationship and for the sensitivity analysis the conditional logistic regression for matched case-control groups.Results By epidemiological surveillance, 1690 suspected episodes of mpox were detected of which 799 were cases and 891 controls.The overall adjusted effectiveness of the pre-exposure vaccination against mpox considering an induction period of 14 days, was 86.4% (95% CI 62.2% to 95.1%). VE increases, with a statistically significant time-response effect, being greater than 77.4% with a 95% confidence level from week 7. The VE at eighth week of vaccination was 99% (95% CI 81.7% to 99.9%).Conclusions The effectiveness of single-dose pre-exposure vaccination against mpox seems very high. Therefore, it appears as a reliable measure to minimise the spread of mpox.The progressive increase in the effectiveness could justify the delay in the administration of the second dose in situations of shortage of vaccines or prioritisation in the vaccination of the maximum number of subjects at risk.Further studies evaluating the long-term effectiveness of the full vaccination would be appropriate.